FATF Recommendations dan Implementasi Nasional: Studi atas Efektivitas Harmonisasi Kebijakan Anti-Money Laundering - M. Ady Soehatman; Ani Purwati; Yuherman (Jurnal Riset Multidisiplin Edukasi, 2025)
Technological developments have had a significant impact on efforts to prevent and combat money laundering. In this context, it is necessary to harmonize Indonesia's Anti-Money Laundering legal system with the recommendations of the Financial Action Task Force as part of global efforts to combat money laundering. This study aims to analyze the normative framework of Indonesia's anti-money laundering policies in implementing FATF Recommendations, with a focus on the effectiveness of regulations for preventing and combating money laundering. The research method used is a normative legal approach, incorporating regulatory, conceptual, and comparative perspectives. The results of the study indicate that Indonesia still needs to harmonize its national legal framework with the FATF Recommendations. Therefore, further efforts are needed in Indonesia to strengthen an effective legal framework for combating money laundering.